Distribuição espacial, amostragem sequencial e dinâmica populacional de Leptopharsa heveae (Hemiptera: Tingidae) na cultura da seringueira - Simonato, Adriano Luís [UNESP] (2014)
With the expansion of rubber trees in the northwestern region of São Paulo state, Brazil, the rubber-tree lacebug, Leptopharsa heveae, reached population levels that caused and continues to cause damages to heveiculture, reducing significantly the rubber production in these trees. To determine the spatial distribution of the lace bug and devise measures to control this pest, experiments were established in 3 areas where RRIM 600 rubber tree clones had been planted (ages 4, 8, and 12 years old), in a farm in the city of Guapiaçu, São Paulo. In each area, 100 parcels were considered, each one made by a line of 3 plants, being sampled 1 branch from the outer section of the lower-third of the canopy of the central plant in each parcel where the number of lacebug nymphs and adults was counted in 27 sampling dates. In each sample, the level of pest aggregation was studied by the dispersion indexes: variance/mean relationship, Morisita's index, Green's coefficient, Taylor's Power Law, and k exponent of the negative binomial; thus, it was verified that, in most samples, the L. heveae population presents aggregate distribution both for nymphs and adults, as well as the pest population as a whole (nymphs plus adults). The adjustment to the probability's distributions was studied through the chi-square test; the binomial negative distribution was the most appropriate model to represent the spatial distribution of the nymphs, adults, and the total population in the 3 areas. A sequential sampling plan was developed for the whole L. heveae population, with an expected maximum of 21 branches being sampled to determine whether preventive measures are necessary. The highest population averages of nymphs and adults of L. heveae occurred from July to October. It was found that the population of L. heveae was significantly influenced by rainfall, regardless of the age of the rubber trees